MENINGKATKAN PERILAKU ENTREPENEURSHIP KARYAWAN MELALUI KEPERCAYAAN TERHADAP PIMPINAN DAN STRUKTUR ORGANISASI - Sugiharti, Sugiharti (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Employe entrepreneurial behavior are considered to be an important driver of innovation and strategic renewal within companies. This paper focuses on employee behaviour and how it can be stimulated towards entrepreneurship. We propose and test a two-step model where formal and informal work context affects employeesâ entrepreneurial behaviour, which then provides the basis for bottom-up initiated entrepreneurial projects. Our empirical data consist of questionnaire responses of 176 employees in Star Hotel Semarang. The results of structural equation model estimations indicate that organisational structure affect employeesâ entrapreneurial behaviour, but also trust in the direct manager. We also find that innovativeness and personal initiative, but not risk taking, play a role for an effective translation of employeesâ behaviour into entrepreneurial projects